The human body book - Parker, Steve (Dorling Kindersley, 2013)
An expanded and enhanced edition of this best selling book. Every aspect of the body's anatomy and function is revealed with remarkable clarity and detail in hundred of 3-D images. Discover how and why the body malfunctions, with easy-to-understand, illustrated analysis of some of the most common disorders. A unique DVD-Rom contains electrifying, specially commissioned animations and allows readers to interact with each body system.